Handbook of radioactivity analysis - L'Annunziata, Michael F. (Academic Press, 1998)
Handbook of Radioactivity Analysis is written by experts in the measurement of radioactivity. The book describes the broad scope of analytical methods available and instructs the reader on how to select the proper technique. It is intended as a practical manual for research which requires the accurate measurement of radioactivity at all levels, from the low levels encountered in the environment to the high levels measured in radioisotope research. This book contains sample preparation procedures, recommendations on steps to follow, necessary calculations, computer controlled analysis, and high sample throughput techniques. Each chapter includes practical techniques for application to nuclear safety, nuclear safeguards, environmental analysis, weapons disarmament, and assays required for research in biomedicine and agriculture. The fundamentals of radioactivity properties, radionuclide decay, and methods of detection are included to provide the basis for a thorough understanding of the analytical procedures described in the book. Therefore, the Handbook can also be used as a teaching text. Key Features * Includes sample preparation techniques for matrices such as soil, air, plant, water, animal tissue, and surface swipes * Provides procedures and guidelines for the analysis of commonly encountered natural and man-made environmental radionuclides * Covers high-sample-throughput microplate techniques and multi-detector scintillation proximity assay methods * Describes the time-saving techniques of computer protocol-controlled automatic activity analysis * Discusses absolute activity measurement methods for meeting scientific reporting requirements * Presents the latest methods of rapid electronic radionuclide imaging * Written by experts in the measurement of radioactivity.